VOLCANIC ACTIVITY IN THE KARYMSKY CENTER IN 1996: SUMMIT ERUPTION AT KARYMSKY AND PHREATOMAGMATIC ERUPTION IN THE AKADEMII NAUK CALDERA - Muraviev Y.D.; Fedotov S.A.; Budnikov V.A.; Ozerov A.Y.; Maguskin M.A.; Dvigalo V.N.; Andreev V.I.; Ivanov V.V.; Kartasheva L.A.; Markov I.A. (My University, 1998)
This paper presents the results of investigating the 1996 eruptive activity of volcanoes in the long-lived Karymsky volcanic center of Kamchatka, where eruptions began simultaneously at Karymsky volcano and in the Akademii Nauk caldera. Renewed effusive and explosive activity occurred at Karymsky after a 14-year period of dormancy and produced ~ 30 million tonnes of andesitic material over the year. The long history of eruptive activity at this volcano is forecast for the next few years. Simultaneously with this activity, which is typical for Karymsky, a subaqueous explosive eruption occurred 6 km to the south in a lake filling the Akademii Nauk caldera, the first event during historic times. A cone of basalt and basaltic andesite pyroclastic material, with a crater 650 m across, grew during an 18-hour period of activity in the northern part of Lake Karymskoe. The volume of this material is estimated as 0.04 km3, and the weight as > 70 million tonnes. The impact of the eruptions on the environment are discussed, the revived hydrothermal activity (new hot springs) in the caldera are described, and breach floods from the lake and other hazards are estimated.